(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2022)
The article is devoted to the problem of incorrect understanding of such a relevant today phenomenon as looting, responsibility for which is provided for in Art. 432 of the current Criminal Code of Ukraine. An attempt has been made to show in detail the true content of the objective and subjective features of the legal composition of the considered socially dangerous phenomenon with a simultaneous comparative analysis of it with some criminal offenses against property, which, like looting, involve the taking of property, in particular in the form of theft. The relevance of the research is noted, due to the lack of adequate coverage of the content of looting. Certain opinions of other researchers regarding some signs of such a criminal act are highlighted, and arguments of both a supporting and refuting nature are given. Attention is drawn to the fact that looting, although it is a robbery in its content, is only a special manifestation of it, connected with a number of signs, only in the presence of which it will take on the appearance that will characterize it in essence. At the same time, the impossibility of a free, not related to the textually expressed form of looting in the norm of its criminal legal interpretation is indicated. At the same time certain comments of extended content are quite admissible, where it does not contradict the characteristics of the action under consideration (characteristics defined in Article 432 of the Criminal Code of Ukraine). It has been noted that the question of the qualification of looting is a question of the need to determine the conformity of the signs of an act actually committed, potentially considered as looting, with the signs that characterize such an act normatively, taking into account the rules and approaches to understanding such a phenomenon as a war crime laid down in legislation. Moreover, cases of actions that resemble looting in appearance, but committed by civilians, as well as representatives of Russian units and persons supported by them from illegal armed formations fighting on the other side, have been differentiated.